Endothelin-3 induced mesenteric vasoconstriction and PMN infiltration in the rat small intestine: role of endothelin receptors - (:unkn) unknown (ELSEVIER SCIENCE BV, 2004)
The objectives of this study were to characterize endothelin (ET)-3-induced alterations in intestinal hemodynamics and to evaluate whether ET-3 administration alters the tissue levels of polymorphonuclear leukocytes (PMNs) and modulates the epithelial barrier function of the small intestine. ET-3 (100 pmol/kg/min) was infused into the superior mesenteric artery (SMA) for 10 min, and tissue samples were obtained 30 min after terminating the infusion. SMA blood flow was significantly decreased throughout the experiment following ET-3 infusion. Pretreatment with bosentan (ET-A and ET-B receptor antagonist), ET-B receptor antagonist BQ-788 or ET-A receptor antagonist BQ-485 completely inhibited the ET-3-induced decrease in the SMA blood flow. Similar results were obtained from the resistance data, in which ET-3-induced increases in SMA resistance were significantly reduced by all ET receptor antagonists. ET-3 administration significantly elevated tissue MPO activity, blood-to-lumen clearance of Cr-51-EDTA and caused a marked microscopic damage in the intestinal mucosa. ET-3-induced elevations in tissue PMN infiltration and mucosal damage were significantly inhibited by pretreatments with ET-A or ET-B receptor antagonists. Overall, our data indicate that ET-3 causes microscopic damage, PMN infiltration and mucosal dysfunction in the rat small intestine. In addition, ET-3-induced hemodynamic alterations as well as tissue PMN infiltration and mucosal damage are mediated by both ET-A and ET-B receptors. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: mucosal injury; BQ-485; BQ-788; mesenteric vasoconstriction; ET(B) RECEPTORS; CONSCIOUS RATS; ETB RECEPTORS; SMOOTH-MUSCLE; IN-VIVO; ET(A); MECHANISMS; IMMUNOREACTIVITY; INFLAMMATION; CONTRACTION